The Effects of College Student Experience on Degree Aspirations for Graduate Education. (August 2022) - Lin, Ching-Hui; Chen, Jyun-Hong; Lin, Eric S.; Lo, C. Owen
The expansion of higher education in Taiwan has significantly increased the number of college students, including substantial growth of those studying at the master's degree level. While prior research indicates that the quality of institutions affects students' achievements, there have been no empirical investigations of how college experiences shape students' educational aspirations for pursuing graduate education. In this study, we applied hierarchical generalized linear model analytics to national student survey data to examine the factors that contribute to students' aspirations for pursuing graduate and professional education. The results revealed that gender, admission types, minority status, financial support, SES, academic preparation, college choice, education expectations, college experience domain, and social integration were significantly related with institutional quality, which further affected progression to the next level of education. The findings highlighted the importance of collegiate experiences and suggested that institutions should provide supporting services for students in the profession of student affairs.